The innate defenders: a review of natural killer cell immunotherapies in cancer - Álvarez-Carrasco, Pablo; Maldonado-Bernal, Carmen (Frontiers in Immunology, 2024)
Cancer is a condition that has been with us for centuries; however, the therapies that have been developed are often associated with significant toxicity and various side effects. Recent advances in immunology have revealed the potential of the immune system to fight cancer, leading to the emergence of immunotherapy. This review focuses on Natural Killer (NK) cells, innate immune effectors with a remarkable ability to directly kill cancer cells. We will explore the historical context of cancer treatment, the nature of NK cells, and the ways they have been developed to enhance their anti-tumor function, highlighting the limitations of conventional therapies. The therapeutic potential of NK cell-based immunotherapies will also be discussed, emphasizing their unique advantages over other immune cell-based approaches. This review highlights the promising future of NK cell therapies in the fight against cancer and their possible application to assist and improve conventional therapies developed so far.